Representation of Youth in Palembang City in Realizing a Collective Movement Rejection of The Increased Fuel Policy in 2022 - Nofrima, Sanny; Baidawi, Ahmad; Saputra, Herdin Arie (Universitas Negeri Semarang, 2023)
This research is motivated by the policy of increasing fuel oil that is still hitting Indonesia. Representation which is one of the responses to form a collective movement that expresses a high level of concern about certain issues. Collective action can achieve the common goal of fighting an organized and powerful authority. This study aims to find out how the students of Palembang City represent in realizing the collective movement against the increase in fuel oil policy by using quantitative methods to find responses in responses or representations of the increase in fuel oil policy. Data was collected from Palembang City students using the slovin formula so as to get 100 respondents in student representation, using three indicators that affect representation, namely; economy 0.363 percent, social media 0.410 and attitude change 0.456 percent. Changes in attitudes in the representation of Palembang City students in realizing collective movements greatly influenced the policy of increasing fuel oil with the highest percentage of 0.456.